Implementasi Pendidikan Spiritual Melalui Pembiasaan dalam Membentuk Karakter Siswa - Irwanto Irwanto (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2021)
Religion exists as a way of life for humans. The spiritual side is a space where humans can strengthen their character, especially religiosity, which is transcendent to Allah, God Almighty. The vertical relationship of man to his God is not solely for personal gain. However, it must also impact social life and humanity in general, meaning that from the spiritual side, it is required to form other positive characters, and it is hoped that a balance between reason and instinct, spiritual intelligence and intelligence will be realized. This study uses qualitative methods. Data collection techniques use interviews, observation, and documentation. Nahdlatul Ulama High School (SMANU) is one of the educational institutions that implement spiritual education through religious rituals with the habituation of toriqoh. Ulama is spiritual education through religion that SMANU carries out is an actual implementation in instilling spiritual values ​​both robbaniyah and insaniyah, which is implemented in the form of scheduled religious activities starting from daily, weekly, monthly, semester, and yearly, which allows students embedded spiritual values ​​that are connected to the formation of character.